Pemenuhan Nafkah Materiil Narapidana Terhadap Keluarga di Lembaga Pemasyarakatan Kelas II A Bulukumba Perspektif Hukum Islam - Azisah, Wafiq; Asni; Kiljamilawati (Universitas Islam Negeri Alauddin Makassar, 2026)
This study aims to analyze the fulfillment of spousal financial support by prisoners toward their families in Class II A Bulukumba Correctional Institution from the perspective of Islamic law. This research is classified as qualitative in the form of a field study by applying an empirical approach. The data sources are interviews and documentation of prisoners and prison employees. The results of this research indicate that 1) efforts to fulfill the material needs of husbands as prisoners for their families in the Class II A Bulukumba Penitentiary are working in the prison, collaborating with families and utilizing savings. 2) the prison's strategy in helping prisoners in fulfilling their material needs is the existence of an independence development program such as carpentry activities, vehicle washing, plantations, wages from work will be given to prisoners. 3) The view of Islamic law regarding the fulfillment of the husband's livelihood who is a prisoner towards the family, in the Qur'an and the majority of scholars that the livelihood must still be given to the wife adjusted to the husband's ability because of the husband's limitations in fulfilling his obligations, most importantly the husband has tried to provide a living even though it is relatively small. The implications of this study are: 1) the prison should develop an independence development program that focuses on work skills that have high economic value. 2) maintaining cooperation between agencies, both government and private agencies and job training institutions. 3) the importance of a wife to reduce dependence on her husband, so that she can face unexpected situations, such as legal problems that befall her husband without feeling burdened.